Enhanced toughening of the crossed lamellar structure revealed by nanoindentation. (December 2017) - Salinas, Christopher L.; de Obaldia, Enrique Escobar; Jeong, Chanhue; Hernandez, Jessica; Zavattieri, Pablo; Kisailus, David
Abstract: Gastropods shells have evolved to resist the threat of increasingly stronger predators that smash, peal, and crush their shells. Their shells are most commonly constructed from a crossed lamellar microstructure, which consists of an exquisitely architected arrangement of aragonitic mineral and organic encompassing at least four orders of hierarchy. It is this careful control of mineral and organic placement within the entire crossed lamellar structure that yields a four-order of magnitude increase in fracture toughness versus abiotic aragonite. We investigated the effect of differing microstructural orientations on their influence of inter-3rd order lamellar fracture behavior using nanoindentation from the inner layer of the Strombus gigas shell. We observed a significant influence of lamella (plank) orientation and nanoindenter probe on the mechanical properties. The ±45° arrangement of mineral planks found within biological crossed lamellar composites provides a significant enhancement of isotropic resistance to penetration by sharp objects such as jaws and claws. In addition, the ±45° arrangement is able to resist higher loads before failure. This combination of features from the crossed lamellar architecture helped enable species with this shell structure to survive predation for hundreds of millions of years and will also help provide insights into designs of future generations of composites. Graphical abstract: Highlights: 1st order lamellae have at least three different mechanisms of deformation. Specific 3rd order orientations offer invariant resistance to penetration. 3rd order orientations of β=±45° dissipate more energy by plastic deformation.